Investigation of pyrolysis kinetics parameters and thermal behavior of thermochemically modified bagasse for bioenergy potential - Peres, Christiano Bruneli [UNESP]; Rosa, André Henrique [UNESP]; de Morais, Leandro Cardoso [UNESP] (Springer Nature, 2021)
Biomass is considering a source of organic carbon, which can replace fossil resources by using pyrolysis process, therefore an efficient biomass thermal modification technology has been target of so much research. The objective of this work is to study the potential energy of sugarcane bagasse and thermochemically modified bagasse for bioenergy potential for use in heat generation and energy. The thermal analysis was conducted by powder-shaped exposure of the three study samples (SB, AC-1, and AC-2) at three heating rates of (5, 7.5 and 10 °C min−1), it was possible to identify three stages of thermal degradation and study some thermochemical reactions, using two iso-conversional models, Kissinger–Akahira–Sunose (KAS) and Ozawa–Flynn–Wall (OFW) to calculate some kinetic parameters, such as activation energy (Ea) and pre-exponential factor (A). First step was about the devolatilization of volatile matter, moisture, and other substances. Degradation of hemicellulose, cellulose and lignin were shown in a second step. Characterization analyzes, such as SEM–EDX and textural parameters of the samples, show the presence of carbon in samples SB and AC-1. Due to SEM analyzes, morphological differences between the samples are showing as AC-1 and AC-2 samples present a rougher shape with pores, on the other hand, SB sample show a fibrous shape. In conclusion, sugarcane bagasse and thermochemically modified bagasse, show very promising results, for future studies, such as for bioenergy potential.
Keywords: Bagasse waste; Bioenergy; Kinetic study; Pyrolysis; SEM–EDX